2020
DOI: 10.1080/21623945.2020.1775035
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin gene expression in abdominal subcutaneous adipose tissue of obese/overweight humans

Abstract: Cathepsin L1 (CTSL1) and B (CTSB) are lysosomal proteases, of which the expression and activity are impaired in adipose tissue (AT) of obese rodents, indicating AT lysosomal dysfunction. Here we assess the relation between abdominal subcutaneous AT (SCAT) CTSL1 and CTSB gene expression (qRT-PCR), body composition and tissue-specific insulin resistance in 77 overweight/obese (BMI: 225.6–38.6 kg/m 2 ) well phenotyped men and women (61 M/16 F). A two-step hyperinsulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Interestingly, CTSB and CTSL have been shown to substitute TMPRSS2 for viral entry of the Ebola virus, which affects the vasculature in the brain and in peripheral organs 100 , but their role in SARS-CoV-2 remains unknown. Whereas the expression of CTSB in the brain and in multiple peripheral tissues was previously reported 101105, 106, 107 , the high expression of CTSB in the brain vasculature endothelium and of CTSL in the peripheral vascular endothelium at both the mRNA and protein levels was not reported to our knowledge, nor was the absence of TMPRSS2. Our own experiments revealed CTSB expression in endothelial cells, neurons, astrocytes, pericytes and microglia within the human brain neurovascular unit and might indeed provide the basis of a potential explanation for some of the putative SARS-CoV-2- mediated effects on the human blood-brain-barrier 30 as well as some of the observed neurovascular symptoms in COVID-19 patients 30, 81 .…”
Section: Discussioncontrasting
confidence: 52%
“…Interestingly, CTSB and CTSL have been shown to substitute TMPRSS2 for viral entry of the Ebola virus, which affects the vasculature in the brain and in peripheral organs 100 , but their role in SARS-CoV-2 remains unknown. Whereas the expression of CTSB in the brain and in multiple peripheral tissues was previously reported 101105, 106, 107 , the high expression of CTSB in the brain vasculature endothelium and of CTSL in the peripheral vascular endothelium at both the mRNA and protein levels was not reported to our knowledge, nor was the absence of TMPRSS2. Our own experiments revealed CTSB expression in endothelial cells, neurons, astrocytes, pericytes and microglia within the human brain neurovascular unit and might indeed provide the basis of a potential explanation for some of the putative SARS-CoV-2- mediated effects on the human blood-brain-barrier 30 as well as some of the observed neurovascular symptoms in COVID-19 patients 30, 81 .…”
Section: Discussioncontrasting
confidence: 52%
“…However, a recent study reported that CTSB mRNA expression in SCAT was unrelated with BMI or WHR but negatively correlated with whole-body insulin resistance in middle-aged individuals with obesity (age 52 ± 2 years). 17 This difference may be due to different subject characteristics (age and BMI). CTSL mRNA expression was also upregulated in the omental AT of the OB group in our study and was strongly related to CTSB mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric phenotyping was performed according to a previously described method. 17 Peripheral blood was drawn in the morning after fasting for at least 8 hours for laboratory analysis, including fasting glucose levels, lipid profile and fasting insulin levels. Glucose levels, glycosylated hemoglobin (HbA1c) levels and lipid profiles including plasma triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and total cholesterol (TC) llevelswere measured using Auto-biochemical Analyzer (Olympus, Japan) by standard techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alterations attenuate the maturation of CSTL, causing the accumulation of autophagosomes, and the consequent, suppression of autophagic clearance (Inami et al, 2011;Mizunoe et al, 2017, Mizunoe et al, 2019. Moreover, increased CTSL and decreased CTSB expression at the transcriptional level have been recently observed in abdominal subcutaneous adipose tissue of overweight/obese men and women, but further research is required to establish whether such changes impact protein levels and activity (Xu et al, 2020).…”
Section: Role Of Cathepsins and Autophagy In Obesitymentioning
confidence: 99%